Implementation of Multiliteracy in PAI Learning through Interactive Learning Media - Rismawati Rismawati; Siti Roudhotul Jannah; Choirudin Choirudin (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the implementation of multiliteracy in Islamic Religious Education (PAI) learning through interactive learning media at SMP Negeri 1 Punggur, Central Lampung. In the digital era characterized by massive and diverse information flows, students are required to have multiliteracy skills encompassing textual, digital, media, and cultural literacy. PAI learning, which has tended to use textual and conventional approaches, faces challenges in comprehensively developing students' multiliteracy competencies. This research employs a qualitative approach with a case study method at SMP Negeri 1 Punggur, an accredited A public junior high school that has implemented the Merdeka Curriculum. Data were collected through participatory observation, in-depth interviews with the principal, PAI teachers, and students, as well as documentation studies, then analyzed using the Miles and Huberman interactive model. The results show that the implementation of multiliteracy through interactive media such as learning videos, visual presentations, digital quizzes, simulations, and Canva-based e-modules has been running, although not evenly distributed. Interactive media has proven to play a significant role in increasing learning interest, active participation, and students' understanding of abstract PAI material. However, the development of visual and digital literacy has not been optimal due to limited media use and the lack of explicit integration of multiliteracy in lesson planning and evaluation. This study recommends strengthening multiliteracy-based planning, implementation, and evaluation as well as improving PAI teachers' digital competence through the TPACK approach to achieve comprehensive multiliteracy development.